Focus on systemic lupus erythematosus in Indigenous Australians: towards a better understanding of autoimmune diseases. Issue 3 (27th February 2013) - Vincent, F. B.; Bourke, P.; Morand, E. F.; Mackay, F.; Bossingham, D.
Abstract The incidence and prevalence of autoimmune diseases such as rheumatoid arthritis, primary Sjögren syndrome, scleroderma and systemic lupus erythematosus (SLE) varies with geography and ethnicity. For example, SLE is reported to be more common in populations such as African‐Caribbeans and Indigenous Australians (IA). As well as socio‐economic status, variation in severity of disease may also show ethnic variability. The initial presentation of SLE in IA, in the context of a unique genetic background and distinctive environmental influences, is often florid with a recurring spectrum of clinical phenotypes. These clinical observations suggest a unique pathway for autoimmunity pathogenesis in this population. For instance, the high prevalence of bacterial infections in IA, particularly group A streptococcus, may be a potential explanation not only for increased incidence and prevalence of SLE but also the commonly florid acute disease presentation and propensity for rapidly progressive end organ threatening disease. This article will review the state of research in autoimmune disease of IA, consider key findings related to autoimmune disease in this population and propose a model potentially to explain the involvement of innate immunity and chronic infection in autoimmune disease pathogenesis. Ultimately, understanding of SLE at this level could affect management and result in personalised and targeted therapies to improve the health status of IA as well as better understanding of SLE pathogenesis per se.